Ovarian metastasis from nongynecologic primary sites: a retrospective analysis of 177 cases and 13-year experience - Jing-Jing Zhang; Dong-Yan Cao; Jia-Xin Yang; Keng Shen (BMC, 2020)
Abstract Background Metastasis to the ovary from nongynecologic organs accounts for 9% of all ovarian malignancies. Although the most common nongynecologic primary site of ovarian metastasis is the gastrointestinal tract, metastasis from other sites to the ovary is not uncommon. Differential diagnosis of primary and metastatic ovarian tumors is important; otherwise, appropriate treatment cannot be determined. Furthermore, an optimal treatment strategy for ovarian metastasis from nongynecologic primary sites still needs to be explored. Methods One hundred seventy-seven patients with ovarian metastasis from nongynecologic primary sites admitted to Peking Union Medical College Hospital between May 2005 and May 2018 were retrospectively evaluated. Results The mean age was 48 years (range, 18-83). Approximately 60% of patients were premenopausal women. The two most common nongynecologic primary sites of ovarian metastasis were the colorectum (68 cases) and stomach (61 cases). In addition to the most common symptoms of abdominal distension (39.0%), abdominal pain (37.9%), and ascites (27.7%), 18.1% of patients presented with abnormal uterine bleeding. Half of the patients who tested serum CA-125 preoperatively had elevated CA-125 levels within the range of 35 U/ml to 200 U/ml. More than 70% of synchronous ovarian metastases were preoperatively misdiagnosed as primary ovarian cancer. Of all included cases, 56.5% achieved optimal cytoreductive surgery (the diameter of the largest residual lesion < 2 cm). The overall 5-year survival rate and median survival time were 10% and 20 months, respectively. The primary site, optimal cytoreductive surgery, tumor differentiation, and postoperative adjuvant treatment were identified as prognostic indicators. Conclusions The colorectum and stomach are the most common nongynecologic primary sites of ovarian metastasis. Synchronous ovarian metastasis is easily misdiagnosed as primary ovarian cancer. Optimal cytoreductive surgery and postoperative adjuvant treatment can be performed to confer survival benefit in selected patients.